Pendidikan Moral Seksualitas Kristiani pada Anak dalam Keluarga Katolik Seturut Terang Ajaran Gereja Familiaris Consortio - Julianti, Victoria; Avan , Komela; Yuda , Yohanes (Vocat : Jurnal Pendidikan Katolik, 2025)
This study  aims to explore and describes the implementation of Christian moral sexuality education for children in Catholic families at Stasi Keluarga Kudus Nazaret Long Bagun based on the teachings of the Church, Familiaris Consortio.  The rtudy is conducted from December 2024 to April 2025. The research utilized a qualitative approach with document study and in-depth interviews involving parents and the Parish Pastor. Data analysis involved technique triangulation and source triangulation. The findings indicated that open communication and gradual education were the main principles in teaching children about sexuality. Parents played an active role by creating an open atmosphere within the family, explaining moral values according to the child's developmental stage, and addressing the challenges that arise in the education process. The conclusion of this research shows that moral sexuality education in Catholic families must be carried out with a wise and loving approach, and requires support from the Church to provide a deeper understanding to parents.